Wet distillers grain and solubles vs. wet corn gluten feed for newly received and growing cattle - Schlegel, Ethan R.; Oleen, Brandon E.; Hollenbeck, William R.; Montgomery, Sean P.; Vahl, Christopher I.; Blasi, Dale A. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2013)
In many instances, due in part to price per unit of energy and proximity to production, Kansas beef producers have the opportunity to incorporate grain-processing byproducts such as wet distillers grains with solubles (WDGS) and wet corn gluten feed (WCGF) into diets for newly received and growing cattle. Although a number of previous studies have compared these two byproducts for use in finishing diets, little information is available for receiving and growing cattle diets. Therefore, the objective of this study was to compare the performance outcomes of newly arrived and growing calves fed either WDGS or WCGF relative to a standard corn-based diet.
Keywords: Cattle; Distillers grain; Wet distillers grains with solubles (WDGS); Wet corn gluten feed (WCGF); Growth performance